Perceived Toxic Leadership, Job Satisfaction, and Organizational Commitment: A Correlational Quantitative Study (Journal of Asian Development Studies, 2025)
This study examined the relationships between perceived toxic leadership (PTL), job satisfaction, and organizational commitment (OC) among Pakistani employees working in Pakistan and the United Arab Emirates (UAE). A cross-sectional correlational research design was employed, and data were collected from 120 participants using purposive sampling. Standardized instruments included the Toxic Leadership Scale (Schmidt, 2008), Minnesota Satisfaction Questionnaire (Weiss et al., 1967), and Organizational Commitment Scale (Allen & Meyer, 1990), all demonstrating satisfactory reliability. Correlation analyses indicated that PTL was strongly negatively associated with job satisfaction (r = −.81, p < .01) and moderately negatively associated with OC (r = −.52, p < .01), while job satisfaction was positively correlated with OC (r = .55, p < .01). Regression analyses showed that PTL significantly predicted lower job satisfaction (β = −.81, p < .001, R² = .69) and lower OC (β = −.52, p < .001, R² = .27). Independent samples t-tests revealed no significant differences in PTL (t(118) = 1.77, p = .07, Cohen’s d = 0.32) or job satisfaction (t(118) = −1.81, p = .07, Cohen’s d = 0.33) between employees in Pakistan and the UAE, but OC was significantly higher among UAE employees (t(118) = −3.37, p = .001, Cohen’s d = 0.61). These findings highlight significant associations between toxic leadership perceptions and employee attitudes and indicate contextual differences in organizational commitment across work environments.